Hungary: Strict Agricultural Land and Holding Regulations for Sustainable and Traditional Rural - Szilágyi, János Ede (Acquisition of Agricultural Lands, 2022)
Hungarian land law is a dynamically changing area of Hungarian law. In the first few years after the regime change of 1989–90, the legislator reregulated this area—which had previously been, in a sense, underregulated—with the Arable Land Act of 1994, thus creating a regulatory environment in which many elements of the current national land law, such as the restrictions on the acquirement of land by legal persons and the system of preemption and prelease rights, were already present. Meanwhile, in parallel, the process of restitution for Hungarian agricultural lands and holdings, which was an important element in the restructuring of former large-scale socialist enterprises to capitalist conditions, was taking place. The restitution process settled many things, but it also became the source of many problems, the effects of which are still felt today. The next major change in Hungarian land law was linked to Hungary’s accession to the EU. For 10 years after the accession in May 2004, Hungarian land legislation was temporarily allowed to maintain its previous national rules. The central element in the creation of EU-compliant regulation is Act CXXII of 2013 on Land Transfer, based on the Hungarian Constitution (the so-called Fundamental Law), and many other laws and regulations supplementing it. In designing this regulatory model, the legislator has sought to ensure both to guarantee the right to property and protect agricultural land as a priority natural resource and national asset protected by the Constitution. It has brought a major change to the Hungarian land law that, in addition to agricultural land, agricultural holding has become one of the central subjects of regulation, and the legislator has now moved toward a special regime for intestate succession of agricultural land. In relation to the regulation of agricultural land, important judgments have now been handed down by both the Hungarian Constitutional Court and the Court of Justice of the European Union. The regulatory framework provided by regional investment protection agreements is an important benchmark in Hungarian land law.Keywords: acquirement of agricultural land, acquirement of agricultural holdings, case law of the Constitutional Court, case law of the Court of Justice of the European Union